Fairy Tale as a Pedagogical Tool for Children under the Age of 3: Educators’ Views and Practices - Sotiropoulou, Eleni; Kasapi, Chrysoula (Global Journal of Educational Studies, 2024)
Fairy tales are undoubtedly the most popular type of literature for children, as they offer pleasure and allow them to travel to unique and fantasy places. However, their value is not limited to entertainment alone, as there are multiple additional benefits from children’s exposure to fairy tales: Fairy tales can contribute to children’s holistic development and therefore they are an excellent pedagogical tool for educators. The aim of this study is to evaluate the views of 213 educators working in nursery schools in Attica (Greece), on the contribution of fairy tales in the development of children under 3 years of age, using a research questionnaire with close-ended questions. Also, this study explores the techniques used by the educators to introduce fairy tales in the pedagogical process, and the domains targeted to attain children’s development by using these fictional narrations. The results of the research show that educators use the fairy tale in children under 3 years of age, primarily to improve the domain of their language development and the most common technique for introducing the fairy tale into pedagogical practice is simply storytelling. Finally, the present study attempts to contribute to research bibliography, showing the importance of fairy tales to a child’s development and at the same time fill the research gap that exists for children under 3 years of age.